Empowering Communities Through Knowledge Sharing in Circular Waste Practices: Plastic Recycling, Maggot-Based Organic Waste Processing and Sustainable Layer Farming at Bening Saguling Foundation - Nugraha Sugiarta; Zulfanida Nurul Sadiyyah; Dewi Christina Marbun; Shinta Hartini Putri; Anggita Lestari; Faisal Reza; Nisa Lathifah; Dave Matthew; Alinda Dwi Yulianti (CV. Proaksara Global Transeduka, 2026)
Increasing environmental challenges and the growing volume of waste have highlighted the need for sustainable and community-based waste management approaches. However, limited public awareness and lack of practical knowledge remain major barriers to the implementation of circular economy practices at the community level. This study examines the role of knowledge sharing in empowering communities through the implementation of circular waste practices at the Bening Saguling Foundation, West Bandung Regency. The program integrates plastic recycling, maggot-based organic waste processing, and sustainable layer farming as a comprehensive approach to waste utilization and community development. This research employs a qualitative approach with a case study design to explore the processes and impacts of an international community service program (PkM).Data were collected through direct observation, interactive discussions, and participant involvement during the program activities. The findings reveal that knowledge sharing, supported by participatory communication and hands-on practices, significantly enhances community understanding and engagement in circular waste management. Participants demonstrated improved awareness of circular economy principles and the ability to apply waste processing techniques, particularly in utilizing maggots as an alternative feed in layer farming systems. However, the sustainability of program implementation remains a challenge, highlighting the need for continuous mentoring and institutional support. Overall, the integration of knowledge sharing and practical training within a circular framework proves effective in strengthening community capacity and promoting sustainable environmental practices. This study contributes to the development of a replicable model for community empowerment based on integrated waste management.